STUDENTS’ PERCEPTION AND MOTIVATION TOWARD ENGLISH E-LEARNING DURING COVID-19 PANDEMIC AT NINTH GRADE OF MTSN 1 SERANG CITY - Fenty Nurhayati Nufus; Anita Anita; Tatu Siti Rohbiah (FKIP, Universitas Banten Jaya, 2022)
COVID-19 pandemic has resulted in the shifting of teaching-learning process replacing with E-learning. This research aimed to knowing the students' perception and motivation towards English E-Learning during Covid-19 pandemic at MTSN 1 Serang City. This research generally answered two questions as follows: 1) What are students’ perception toward English E-learning during covid-19 pandemic? 2) How are students’ motivation toward English E-learning during covid-19 pandemic?. In this research the technique of collecting data researcher used interview and questionnaire method. There were 20 students of ninth graders at MTSN 1 Serang City participated in this research. The research instrument of this research is researcher herself. Since this research explored the students’ perception and motivation which coming from the students’ experiences during covid-19 pandemic, this research was applied descriptive qualitative design. The findings from the data analysis, students give positive perception toward English E-learning, because the process of learning English is easier with E-learning and E-learning can foster students’ interest and motivated in learning English. Even though students found problems in implementing English E-learning, students also found learning English through E-Learning is quite effective.